2005
DOI: 10.1177/156482650502600102
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Homestead Gardening Program on Household Food Security and Empowerment of Women in Bangladesh

Abstract: This paper assesses the additional benefits of a homestead gardening program designed to control vitamin A deficiency in Bangladesh. In February and March 2002, data were collected on the food security and social status of women from 2,160 households of active and former participants in the gardening program and from control groups in order to assess the impact and sustainability of the program. The proportions of active and former-participant households that gardened year-round were fivefold and threefold, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
103
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(117 citation statements)
references
References 12 publications
(18 reference statements)
8
103
0
1
Order By: Relevance
“…Assessments of home stead food production systems in Bangladesh and Nepal report positive eff ects on women's income, control over resources, or infl uence in decision making on a range of issues. 53,[61][62][63] In Kenya, a project promoting orange sweet potato production among women farmers showed that women gained control over selling the product, whereas men maintained control over income. 64 Livestock and dairy projects in Kenya and Bangladesh report increases in women's income or infl uence in decision making, 65,66 whereas in India, men's but not women's income improved as a result of a dairy project.…”
Section: Home Gardens and Homestead Food Production Systemsmentioning
confidence: 99%
“…Assessments of home stead food production systems in Bangladesh and Nepal report positive eff ects on women's income, control over resources, or infl uence in decision making on a range of issues. 53,[61][62][63] In Kenya, a project promoting orange sweet potato production among women farmers showed that women gained control over selling the product, whereas men maintained control over income. 64 Livestock and dairy projects in Kenya and Bangladesh report increases in women's income or infl uence in decision making, 65,66 whereas in India, men's but not women's income improved as a result of a dairy project.…”
Section: Home Gardens and Homestead Food Production Systemsmentioning
confidence: 99%
“…Dietary outcomes are probably the more appropriate outcome in which to expect to see an impact (ISPC 2014). Some studies suggest that, in some cases, a lack of effect is due to the fact that garden produce may replace other nutritious foods in the diet (Bushamuka et al 2005) or that the degree of women's control of income earned can also impact success (Brun et al 1989).…”
Section: Home Gardensmentioning
confidence: 99%
“…In addition, for the subset of UA composed of home and community gardening, a wide body of observational studies report health benefits, such as increasing food security (Bushamuka et al, 2005;Stroink & Nelson, 2009), fruit and vegetable intake (Alaimo, Packnett, Miles, & Kruger, 2008;Armstrong, 2000;Litt, Soobader, Turbin, Hale, Buchenau, & Marshall, 2011;Twiss, Dickinson, Duma, Kleinman, Paulsen, & Rilveria, 2003), and physical activity (Armstrong, 2000;Draper & Freedman, 2010;Park, Shoemaker, & Haub, 2009), while reducing stress (Hawkins, Thirlaway, Backx, & Clayton, 2011;Van Den Berg & Custers, 2011). Building social capital is another documented community and community health-related benefit of gardening (Alaimo, Reischl, & Allen, 2010;Firth, Maye, & Pearson, 2011;Kingsley & Townsend, 2006).…”
Section: Introductionmentioning
confidence: 99%